2016
DOI: 10.1021/acsami.6b11821
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Coupled FeNi Alloys/NiFe2O4@Carbonitride Layers-Assembled Microboxes for Enhanced Oxygen Evolution Reaction

Abstract: Hydrogen produced from electrocatalytic water splitting is a promising route due to the sustainable powers derived from the solar and wind energy. However, the sluggish kinetics at the anode for water splitting makes the highly effective and inexpensive electrocatalysts desirable in oxygen evolution reaction (OER) by structure and composition modulations. Metal-organic frameworks (MOFs) have been intensively used as the templates/precursors to synthesize complex hollow structures for various energy-related app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 62 publications
6
70
0
2
Order By: Relevance
“…In addition, 89% of the initial current was maintained after 8 h by a chronopotentiometry method, further verifying the good stability of Ni 2 P/Ni@C catalyst in acid electrolyte. The outstanding durability of Ni 2 P/Ni@C catalyst should be attributed to the Ni 2 P/Ni nanocomposite delicately embedded in porous carbon shell, preventing it from agglomerating and pulverizing . Besides, in order to demonstrate the advantages of MOF‐derived route, the synthesis, characterization, and electrochemical performance of Ni 2 P/Ni/C from a sol–gel route (using citric acid as an agent) were also investigated for comparison (Figures S10–S14 and Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 89% of the initial current was maintained after 8 h by a chronopotentiometry method, further verifying the good stability of Ni 2 P/Ni@C catalyst in acid electrolyte. The outstanding durability of Ni 2 P/Ni@C catalyst should be attributed to the Ni 2 P/Ni nanocomposite delicately embedded in porous carbon shell, preventing it from agglomerating and pulverizing . Besides, in order to demonstrate the advantages of MOF‐derived route, the synthesis, characterization, and electrochemical performance of Ni 2 P/Ni/C from a sol–gel route (using citric acid as an agent) were also investigated for comparison (Figures S10–S14 and Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency and performance of the present catalytic electrodes are comparable or superior to the powder electrocatalysts and catalytic electrodes based on [Ni,Fe]O nanoparticles reported earlier (and also commercially available catalysts like Ir/C and IrO 2 ) (Table S5). [24] The advantage of our strategy in terms of the ease and simplicity of catalyst electrode fabrication is revealed by the comparison with earlier reported methods involving temperatures up to 500°C and multiple steps with processing times ranging from 3-48 h. [27,[40][41][42][43][44] Even though electrodeposition is a simple approach and provides electrocatalysts with high efficiency and extended stability seen in chronoamperometric experiments, careful examination of the electrodes have revealed liberation of iron from the anode and its deposition on the cathode; [2] such catalyst composition changes are detrimental for practical applications. In some cases, dissolution of the surface-bound catalyst had to be compensated by adding the metal ions in the electrolyte.…”
Section: Communicationsmentioning
confidence: 99%
“…So, it is promising to prepare an analogous MOF‐74 as the precursor for ORR catalysts, getting replacement of DHTA by DHBA. Because of the variety of MOFs’ morphology, these catalysts derived from MOFs exhibit different morphologies and structures, such as hollow spherical, nanoparticles‐embedded carbon nanotubes and porous carbon, carbon inherited rhombic dodecahedral shapes and microboxes, etc. It has been shown that the properties of these carbon materials have played a vital role in dominating the electrochemical performance of ORR.…”
Section: Introductionmentioning
confidence: 99%